Bi2Se3@MWNTs composite material, preparation method and application, working electrode, and nitrite detection method

By using BI2SE3@MWNTS composite material modification glass carbon electrodes, the problem of expensive materials, poor stability, and potential pollution risks in the wild applications in the wild applications have been solved, and high sensitivity and low detection limit nitrite Salt detection.

CN111796010BInactive Publication Date: 2025-01-28INST OF HYDROGEOLOGY & ENVIRONMENTAL GEOLOGY CHINESE ACAD OF GEOLOGICAL SCI
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202010719365.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2020-07-23
Publication Date
2025-01-28
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

In the field applications of existing electrochemical detection methods, there are problems such as expensive materials, poor stability, potential pollution risks and degraded detection performance, making it difficult to quickly and accurately detect nitrites in groundwater.

Method used

Use BI2SE3@MWNTS composite material to modify the glass carbon electrodes. By synthesizing the BI2SE3@MWNTS composite material and combining it with the glass carbon electrode to form work electrodes used to detect nitrite.

Benefits of technology

The high sensitivity, low detection limit and good stability can be achieved, and nitrite can be accurately detected within the range of 0.02 to 6000 μm to avoid the risk of pollution of metal catalysts.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN111796010B_ABST
    Figure CN111796010B_ABST
Patent Text Reader

Abstract

The present invention provides a Bi2Se3@MWNTs composite material, a preparation method and application thereof, a working electrode, and a method for detecting nitrite. The working electrode comprises a glassy carbon electrode and a Bi2Se3@MWNTs composite material coated on the surface of the glassy carbon electrode. The raw materials of the present invention are cheap and readily available, the preparation method is simple, the obtained Bi2Se3@MWNTs composite material has a large active surface area and a fast electron transfer rate; the obtained working electrode has good reliability and strong stability, promotes the adsorption and oxidation of nitrite, can be used to detect nitrite, has a wide detection range, a low detection limit, high sensitivity, and avoids the problems of electrode poisoning and environmental pollution caused by the use of metal catalysts, which is conducive to application and promotion in actual field surveys.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of electrochemical detection, and in particular to a Bi2Se3@MWNTs composite material, a preparation method and application thereof, a working electrode, and a nitrite detection method. Background Art

[0002] Nitrite (NO2 - ) is one of the more typical pollutants in groundwater. Due to its toxicity, it can pose a huge threat to human health. Therefore, it is necessary to conduct groundwater pollution investigations on the site. The key to pollution investigation is to judge the degree, scope and possible damage of pollution as soon as possible, and to quickly carry out relevant emergency treatment. On-site rapid detection technology can improve the response speed and plays a vital role in responding to and handling environmental pollution incidents. Therefore, the development of simple, fast and accurate detection methods is of great significance to water pollution investigations and public health.

[0003] In recent years, electrochemical methods have attracted much attention due to their inherent advantages such as simple operation, fast response speed and high sensitivity. - Research on detection continues to emerge. In electrochemical sensors, electrode materials are the key to determining sensor performance. With the development of electrochemical detection technology, people have found that when only bare electrodes are used for detection, the current response is often limited. Afterwards, the modified material (catalyst) is attached to the electrode through human intervention to improve the performance of the electrode and improve the performance and response of the electrode. The most commonly used modified materials include precious metal nanoparticles, transition metals, metal oxides / hydroxides, and bimetallic / alloys.

[0004] Since most of the traditional electrochemical detection research is aimed at laboratory analysis and research, the application conditions in the field are basically not taken into consideration. Therefore, there are still many shortcomings in directly using modified electrodes for field water pollution investigations: First, the synthesis of metal nanomaterials is complex and expensive, and the amount prepared in the laboratory is small, so they cannot be obtained on a large scale; second, they are generally unstable and will oxidize and agglomerate after long-term storage, causing a decrease in electrochemical performance; third, metal materials often have certain potential pollution risks, which should be avoided as much as possible for pollution investigations; fourth, when using metal modified electrodes to detect NO2 - When the electrodes are charged, they often interact with each other, poisoning the electrode surface, generating high overvoltage and reducing the detection performance.

[0005] Therefore, how to develop an electrochemical electrode that is environmentally friendly, inexpensive, and has excellent detection performance and is suitable for actual field surveys is one of the key issues that need to be solved urgently. Summary of the invention

[0006] One of the purposes of the present invention is to provide a Bi2Se3@MWNTs composite material.

[0007] The second object of the present invention is to provide a method for preparing a Bi2Se3@MWNTs composite material.

[0008] The third object of the present invention is to provide an application of a Bi2Se3@MWNTs composite material in the preparation of electrochemical electrodes.

[0009] A fourth object of the present invention is to provide a working electrode.

[0010] A fifth object of the present invention is to provide a method for preparing a working electrode.

[0011] A sixth object of the present invention is to provide a nitrite detection system.

[0012] A seventh object of the present invention is to provide a method for detecting nitrite.

[0013] One of the purposes of the present invention is achieved in that:

[0014] A Bi2Se3@MWNTs composite material, wherein the mass ratio of Bi2Se3 to MWNTs is 0.5-1.5, and Bi2Se3 sheets are uniformly distributed on the MWNTs.

[0015] Preferably, the mass ratio of Bi2Se3 and MWNTs is 1:1.

[0016] Preferably, the double layer capacitance C of Bi2Se3@MWNTs dl The value is 1.65 mF·cm -2 , with abundant electrochemical active area.

[0017] The second object of the present invention is achieved in this way:

[0018] The preparation method of the aforementioned Bi2Se3@MWNTs composite material is to disperse Bi2Se3 and MWNTs in a mass ratio of 0.5 to 1.5 in a dispersant and mix them evenly to obtain the Bi2Se3@MWNTs composite material.

[0019] The dispersant includes at least one of DMF, water, tetrahydrofuran, etc. Preferably, the dispersant is DMF.

[0020] The third object of the present invention is achieved in this way:

[0021] The use of the aforementioned Bi2Se3@MWNTs composite material in preparing electrochemical electrodes, in particular, the use of the Bi2Se3@MWNTs composite material and glassy carbon electrode in preparing electrochemical electrodes.

[0022] The fourth object of the present invention is achieved in this way:

[0023] A working electrode, comprising a glassy carbon electrode and a Bi2Se3@MWNTs composite material coated on the surface of the glassy carbon electrode, wherein the coating amount of the Bi2Se3@MWNTs composite material on the surface of the glassy carbon electrode is 0.55-0.85 μg / mm 2 .

[0024] Preferably, the coating amount of the Bi2Se3@MWNTs composite material on the surface of the glassy carbon electrode is 0.65-0.80 μg / mm 2 , more preferably 0.71 μg / mm 2 .

[0025] Preferably, the anode current value of the working electrode is 200 μA.

[0026] Preferably, the charge transfer resistance of the working electrode is 50 Ω.

[0027] The fifth purpose of the present invention is achieved in this way:

[0028] The method for preparing the aforementioned working electrode comprises the following steps:

[0029] (a) dispersing the Bi2Se3@MWNTs composite material in a dispersant to obtain a Bi2Se3@MWNTs composite material solution;

[0030] (b) The Bi2Se3@MWNTs composite material solution is drop-coated on the pretreated glassy carbon electrode surface and dried to obtain the working electrode.

[0031] In step (a), the dispersant is DMF, water, tetrahydrofuran, etc. Preferably, the dispersant is DMF.

[0032] In step (a), the concentration of the Bi2Se3@MWNTs composite material solution is 0.4-0.6 mg / mL, preferably 0.5 mg / mL.

[0033] In step (b), the glassy carbon electrode can be pretreated by an existing pretreatment method. Preferably, the pretreatment of the glassy carbon electrode is to polish the glassy carbon electrode with Al2O3, ultrasonically wash it with H2SO4 aqueous solution, ethanol, and secondary water, respectively, and then blow dry it with N2 flow; specifically, the glassy carbon electrode (GCE) is polished with Al2O3 (0.05 μm, 0.1 μm), ultrasonically wash it with 0.5 M H2SO4, ethanol, and secondary water for 30 s, respectively, and then blow dry it with N2 flow.

[0034] In step (b), the drying is performed by baking under an infrared lamp.

[0035] The working electrode can be used to detect nitrite, especially nitrite in sewage, and its linear detection range for nitrite is 0.02-6000 μM, and the detection limit is 20 nM.

[0036] The sixth object of the present invention is achieved in this way:

[0037] The nitrite detection system includes an electrochemical workstation, the aforementioned working electrode, a reference electrode, a counter electrode, and a test solution contained in a test container, wherein one end of the working electrode, the reference electrode, and the counter electrode are all connected to the electrochemical workstation, and the other ends of the working electrode, the reference electrode, and the counter electrode are all immersed in the test solution.

[0038] The electrochemical workstation is connected to a computer so that the signals generated by the electrochemical workstation can be displayed on the computer.

[0039] The electrochemical workstation used was Chenhua CHI 660D.

[0040] Ag / AgCl electrode (saturated with KCl) was used as the reference electrode.

[0041] A platinum wire was used as the counter electrode.

[0042] The seventh object of the present invention is achieved in this way:

[0043] A method for detecting nitrite comprises the following steps: adjusting the pH value of a sample solution containing nitrite to 6.5-8 to obtain a test solution; inserting a working electrode, a reference electrode and a counter electrode into the test solution, so that the other ends of the working electrode, the reference electrode and the counter electrode are all immersed in the test solution; setting a constant voltage and reading a current value; and converting the current value into a solution concentration value according to a current concentration curve.

[0044] Preferably, the pH value of the sample to be tested is adjusted to 6.5-7.5, more preferably 7.

[0045] Preferably, the voltage of the electrochemical workstation is kept constant at 0.85V.

[0046] The present invention synthesizes a Bi2Se3@MWNTs composite material and uses it to construct a working electrode for detecting nitrite. The obtained Bi2Se3@MWNTs composite material has a large active surface area and a fast electron transfer rate; the obtained working electrode has good reliability and strong stability, promotes the adsorption and oxidation of nitrite, and can be used to detect nitrite, with a wide detection range, a low detection limit, and high sensitivity.

[0047] The raw materials of the invention are cheap and easily available, the preparation method is simple, and the electrode poisoning and environmental pollution problems caused by the use of metal catalysts are avoided, which is conducive to application and promotion in actual field investigations. BRIEF DESCRIPTION OF THE DRAWINGS

[0048] Figure 1 This is the SEM image of Bi2Se3@MWNTs prepared in Example 1.

[0049] Figure 2 This is the TEM image of Bi2Se3@MWNTs prepared in Example 1.

[0050] Figure 3 The CV graph (Figure A) and electrochemical active area (Figure B) of Bi2Se3@MWNTs prepared in Example 1.

[0051] Figure 4 The three electrodes of bare GCE of comparative example 1, Bi2Se3 / GCE of comparative example 2 and Bi2Se3@MWNTs / GCE of example 1 were prepared in the presence of 5.0 mM [Fe(CN)6] 3- / 4- CV graph of 0.1 M KCl solution.

[0052] Figure 5 The three electrodes of bare GCE of comparative example 1, Bi2Se3 / GCE of comparative example 2 and Bi2Se3@MWNTs / GCE of example 1 were prepared in the presence of 5.0 mM [Fe(CN)6] 3- / 4- Electrochemical impedance spectroscopy in 0.1 M KCl solution.

[0053] Figure 6 The three electrodes of bare GCE of comparative example 1, Bi2Se3 / GCE of comparative example 2 and Bi2Se3@MWNTs / GCE of example 1 were heated in 0.1 M PBS (pH=7.0) containing 1 mM NO2 - DPV curve of the solution.

[0054] Figure 7 The Bi2Se3@MWNTs / GCE electrode pair of Example 1 contains different concentrations of NO2 - CV graph of 0.1 M PBS (pH=7.0) solution.

[0055] Figure 8 The Bi2Se3@MWNTs / GCE electrode of Example 1 was continuously injected with NO2 - Current response diagram after adding 0.1M PBS (pH=7.0) solution.

[0056] Fig. 9The Bi2Se3@MWNTs / GCE electrode of Example 1 was continuously injected with NO2 - The current after 0.1M PBS (pH=7.0) solution and NO2 - concentration calibration curve.

[0057] Fig.10 This is the repeatability test result diagram of Bi2Se3@MWNTs / GCE electrode.

[0058] Fig.11 This is the stability test of Bi2Se3@MWNTs / GCE electrode within 6000s.

[0059] Fig.12 For the IT test in PBS (pH = 7.0) solution, the current changes were measured by adding 100 μM of different interferents every 50 s.

[0060] Fig.13 Schematic diagram of the structure of the working electrode, wherein: 1. working electrode; 11. glassy carbon electrode; 12. Bi2Se3@MWNTs composite material.

[0061] Fig.14 It is a schematic diagram of the structure of the nitrite detection system, including: 1. working electrode, 2. reference electrode, 3. counter electrode, 4. electrochemical workstation, 5. test container, 6. test solution, and 7. computer. DETAILED DESCRIPTION

[0062] The present invention is further described below in conjunction with examples. The following examples are only for illustration and are not intended to limit the scope of protection of the present invention in any way.

[0063] The processes and methods not described in detail in the following examples are conventional methods known in the art, and the reagents used in the examples are all analytically pure or chemically pure, and can be purchased commercially or prepared by methods well known to those of ordinary skill in the art. The following examples all achieve the purpose of the present invention.

[0064] Bi2Se3 was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd., product number B119288, density 6.82 g / cm 3 , melting point 710 ° C. Multi-walled carbon nanotubes (MWNTs) were purchased from Jiangsu Xianfeng Nanomaterial Technology Co., Ltd., with a purity greater than 95%, φ = 30-50 nm.

[0065] Comparative Example 1

[0066] The glassy carbon electrode (GCE) was polished with Al2O3 (0.05 μm, 0.1 μm), ultrasonically washed with 0.5 M H2SO4, ethanol, and secondary water for 30 s, respectively, and then dried with N2 flow to obtain the bare GCE used in the experiment.

[0067] Comparative Example 2

[0068] The glassy carbon electrode (GCE) was polished with Al2O3 (0.05 μm, 0.1 μm), ultrasonically cleaned with 0.5 M H2SO4, ethanol, and secondary water for 30 s, respectively, and then treated with N2 flow to obtain a bare GCE.

[0069] Take 1.0 mg of Bi2Se3 in a reagent bottle, add 2 mL of dispersant DMF, and disperse evenly by ultrasonication to obtain a DMF solution of Bi2Se3 solution. 10 μL of DMF solution of Bi2Se3 was uniformly modified on the surface of GCE by drop coating, and the coating range was a circular area with a diameter of 3 mm from the center of the glassy carbon electrode; it was dried under an infrared lamp to obtain a Bi2Se3-modified GCE electrode (Bi2Se3 / GCE).

[0070] Example 1

[0071] The glassy carbon electrode (GCE) was polished with Al2O3 powder (0.05 μm, 0.1 μm), ultrasonically cleaned with 0.5 M H2SO4, ethanol, and deionized water for 30 s, respectively, and finally dried with N2 flow at room temperature.

[0072] 0.5 mg of Bi2Se3 and multi-walled carbon nanotubes (MWNTs) (mass ratio of 1:1) were mixed in a reagent bottle, and then 2 mL of dispersant DMF was added and ultrasonically mixed to obtain a Bi2Se3@MWNTs composite material solution. 10 μL of Bi2Se3@MWNTs composite material solution was uniformly modified on the GCE surface by drop coating, and the coating range was a circular area with a diameter of 3 mm from the center of the glassy carbon electrode; it was dried under an infrared lamp to obtain a Bi2Se3@MWNTs-modified GCE electrode (Bi2Se3@MWNTs / GCE). The modification amount of Bi2Se3@MWNTs composite material was 5 μg, and the modification amount per square millimeter on the electrode was about 0.71 μg.

[0073] The obtained Bi2Se3@MWNTs composite material was characterized by SEM and TEM. Figure 1~2 As shown in the figure, it can be seen that the ultrathin Bi2Se3 sheets are evenly distributed on the MWNTs.

[0074] The cyclic voltammetry (CV) method was used to calculate the double layer capacitance (C dl) to evaluate the electrochemical active area of ​​the material. The cyclic voltammetry curves of Bi2Se3@MWNTs were tested in 0.1M PBS (pH 7.0) solution at different scan rates ( Figure 3 A), and C is calculated based on its current value dl , thus obtaining the electrochemical active area ( Figure 3 B). Figure 3 As shown in B, C dl The value is 1.65 mF·cm -2 , reflecting the large electrochemical specific surface area of ​​Bi2Se3@MWNTs. In this composite material, the conductive MWNTs provide electron transfer pathways, while the Bi2Se3 nanosheets promote the transfer of electrons to the active sites.

[0075] The cyclic voltammetry (CV) and electrochemical impedance spectroscopy (EIS) were used to study the cyclic voltammetry behaviors of the bare GCE of comparative example 1, the Bi2Se3 / GCE of comparative example 2, and the Bi2Se3@MWNTs / GCE of this embodiment. The results are shown in Figure 2. Figures 4 and 5 shown.

[0076] Depend on Figure 4 It can be seen that the current response of bare GCE is the worst, with the anode peak current of only 80μA; the current response of Bi2Se3 / GCE modified with Bi2Se3 is enhanced, with the anode peak current value of 125μA, and the electron transfer rate is improved; and the peak current of Bi2Se3@MWNTs / GCE is the largest, with the anode current value reaching 200μA, indicating that Bi2Se3@MWNTs / GCE has good conductive properties and a faster electron transfer efficiency.

[0077] Depend on Figure 5 It can be seen that the semicircle diameter of Bi2Se3 / GCE is larger, about 70 Ω, showing a higher charge transfer resistance (Ret). The Bi2Se3@MWNTs / GCE electrode shows the smallest semicircle diameter and a relatively low Ret of about 50 Ω, showing the highest charge transfer efficiency. The excellent kinetic characteristics are due to the excellent conductivity of MWNTs, which promotes fast electron migration rate and large interfacial electron capacity transmission, effectively improving the catalytic activity of the composite material.

[0078] Differential pulse voltammetry (DPV) was used to study the NO2 - The electrochemical response of Figure 6 As shown. Figure 6 It can be clearly seen that bare GCE has a significant effect on NO2 - The oxidation current response of Bi2Se3 / GCE to NO2 -The oxidation response of Bi2Se3@MWNTs / GCE is slightly greater than that of bare GCE, indicating that the electrode performance is improved after Bi2Se3 modification, but the current response is still low; - The oxidation current response of Bi2Se3@MWNTs has been significantly improved compared with the previous two, and the oxidation peak potential is the lowest. This is attributed to the large specific surface area, good conductivity and abundant defects of Bi2Se3@MWNTs, which significantly improves and improves NO2 - Adsorption and oxidation reactions at the electrode.

[0079] Example 2

[0080] In 0~5mMNO2 - The electrochemical behavior of Bi2Se3@MWNTs / GCE prepared in Example 1 was tested using CV curves in 0.1 M PBS (pH = 7.0) solution at a concentration of 1.0. Figure 7 As shown. Figure 7 It can be seen that with the increase of NO2 - As the concentration increases, the oxidation peak current increases significantly, indicating that Bi2Se3@MWNTs / GCE can be used to detect NO2 - It is feasible.

[0081] Example 3

[0082] Using PBS buffer solution, NO2 - The pH value of the sample was adjusted to 7, and the electrochemical behavior of the Bi2Se3@MWNTs / GCE prepared in Example 1 was tested by differential pulse voltammetry (DPV), and the response current value was 45.4 μA.

[0083] Example 4

[0084] Using PBS buffer solution, NO2 - The pH value of the sample was adjusted to 8, and the electrochemical behavior of the Bi2Se3@MWNTs / GCE prepared in Example 1 was tested by differential pulse voltammetry (DPV), and the response current value was 41.6 μA.

[0085] Example 5

[0086] Using PBS buffer solution, NO2 - The pH value of the sample was adjusted to 6.5, and the electrochemical behavior of the Bi2Se3@MWNTs / GCE prepared in Example 1 was tested by differential pulse voltammetry (DPV), and the response current value was 42 μA.

[0087] Comparative Example 3

[0088] Using PBS buffer solution, NO2 -The pH value of the sample was adjusted to 5, and the electrochemical behavior of the Bi2Se3@MWNTs / GCE prepared in Example 1 was tested by differential pulse voltammetry (DPV), and the response current value was 31 μA.

[0089] Comparative Example 4

[0090] Using PBS buffer solution, NO2 - The pH value of the sample was adjusted to 6, and the electrochemical behavior of the Bi2Se3@MWNTs / GCE prepared in Example 1 was tested by differential pulse voltammetry (DPV), and the response current value was 36 μA.

[0091] Comparative Example 5

[0092] Using PBS buffer solution, NO2 - The pH value of the sample was adjusted to 9, and the electrochemical behavior of the Bi2Se3@MWNTs / GCE prepared in Example 1 was tested by differential pulse voltammetry (DPV), and the response current value was 38 μA.

[0093] Example 6

[0094] 0.5 mg of Bi2Se3 and MWNTs (mass ratio of 1:1) were mixed in a reagent bottle, and then 2 mL of dispersant DMF was added and ultrasonically mixed to obtain a Bi2Se3@MWNTs composite material solution. The glassy carbon electrode (GCE) was polished with Al2O3 (0.05 μm, 0.1 μm), ultrasonically washed with 0.5 M H2SO4, ethanol, and secondary water for 30 s, and then treated with N2 flow. 9 μL of Bi2Se3@MWNTs composite material solution was uniformly modified on the GCE surface by drop coating, and dried under infrared light to obtain a Bi2Se3@MWNTs modified GCE electrode (Bi2Se3@MWNTs / GCE). The coating amount of Bi2Se3@MWNTs composite material on the surface of the glassy carbon electrode was 0.64 μg / mm 2 .

[0095] Using PBS buffer solution, NO2 - The pH value of the sample was adjusted to 7, and the electrochemical behavior of the prepared Bi2Se3@MWNTs / GCE was tested by differential pulse voltammetry (DPV), and the response current value was 42.0μA.

[0096] Example 7

[0097] 0.5 mg of Bi2Se3 and MWNTs (mass ratio of 1:1) were mixed in a reagent bottle, and then 2 mL of dispersant DMF was added and ultrasonically mixed to obtain a Bi2Se3@MWNTs composite material solution. The glassy carbon electrode (GCE) was polished with Al2O3 (0.05 μm, 0.1 μm), ultrasonically washed with 0.5 M H2SO4, ethanol, and secondary water for 30 s, and then treated with N2 flow. 11 μL of Bi2Se3@MWNTs composite material solution was uniformly modified on the GCE surface by drop coating, and dried under infrared light to obtain a Bi2Se3@MWNTs modified GCE electrode (Bi2Se3@MWNTs / GCE). The coating amount of Bi2Se3@MWNTs composite material on the surface of the glassy carbon electrode was 0.78 μg / mm 2 .

[0098] Using PBS buffer solution, NO2 - The pH value of the sample was adjusted to 7, and the electrochemical behavior of the prepared Bi2Se3@MWNTs / GCE was tested by differential pulse voltammetry (DPV), and the response current value was 43.0μA.

[0099] Example 8

[0100] 0.5 mg of Bi2Se3 and MWNTs (mass ratio of 1:1) were mixed in a reagent bottle, and then 2 mL of dispersant DMF was added and ultrasonically mixed to obtain a Bi2Se3@MWNTs composite material solution. The glassy carbon electrode (GCE) was polished with Al2O3 (0.05 μm, 0.1 μm), ultrasonically washed with 0.5 M H2SO4, ethanol, and secondary water for 30 s, and then treated with N2 flow. 12 μL of Bi2Se3@MWNTs composite material solution was uniformly modified on the GCE surface by drop coating, and dried under infrared light to obtain a Bi2Se3@MWNTs modified GCE electrode (Bi2Se3@MWNTs / GCE). The coating amount of Bi2Se3@MWNTs composite material on the surface of the glassy carbon electrode was 0.85 μg / mm 2 .

[0101] Using PBS buffer solution, NO2 - The pH value of the sample was adjusted to 7, and the electrochemical behavior of the prepared Bi2Se3@MWNTs / GCE was tested by differential pulse voltammetry (DPV), and the response current value was 41.7μA.

[0102] Comparative Example 6

[0103] 0.5 mg of Bi2Se3 and MWNTs (mass ratio of 1:1) were taken and mixed in a reagent bottle, and then 2 mL of dispersant DMF was added and ultrasonically mixed to obtain a Bi2Se3@MWNTs composite material solution. The glassy carbon electrode (GCE) was polished with Al2O3 (0.05 μm, 0.1 μm), ultrasonically washed with 0.5 M H2SO4, ethanol, and secondary water for 30 s, and then treated with N2 flow. 7 μL of Bi2Se3@MWNTs composite material solution was uniformly modified on the GCE surface by drop coating, and dried under infrared light to obtain a Bi2Se3@MWNTs modified GCE electrode (Bi2Se3@MWNTs / GCE). The coating amount of Bi2Se3@MWNTs composite material on the surface of the glassy carbon electrode was 0.50 μg / mm 2 .

[0104] Using PBS buffer solution, NO2 - The pH value of the sample was adjusted to 7, and the electrochemical behavior of the prepared Bi2Se3@MWNTs / GCE was tested by differential pulse voltammetry (DPV), and the response current value was 36.4μA.

[0105] Comparative Example 7

[0106] 0.5 mg of Bi2Se3 and MWNTs (mass ratio of 1:1) were taken and mixed in a reagent bottle, and then 2 mL of dispersant DMF was added and ultrasonically mixed to obtain a Bi2Se3@MWNTs composite material solution. The glassy carbon electrode (GCE) was polished with Al2O3 (0.05 μm, 0.1 μm), ultrasonically washed with 0.5 M H2SO4, ethanol, and secondary water for 30 s, and then treated with N2 flow. 5 μL of Bi2Se3@MWNTs composite material solution was uniformly modified on the GCE surface by drop coating, and dried under infrared light to obtain a Bi2Se3@MWNTs modified GCE electrode (Bi2Se3@MWNTs / GCE). The coating amount of Bi2Se3@MWNTs composite material on the surface of the glassy carbon electrode was 0.36 μg / mm 2 .

[0107] Using PBS buffer solution, NO2 - The pH value of the sample was adjusted to 7, and the electrochemical behavior of the prepared Bi2Se3@MWNTs / GCE was tested by differential pulse voltammetry (DPV), and the response current value was 33.0μA.

[0108] Example 9

[0109] The Bi2Se3@MWNTs / GCE electrode prepared in Example 1 was used to continuously add different concentrations of NO2 in 0.1 M PBS (pH=7) at a voltage of 0.85 V. - The current response of Bi2Se3@MWNTs / GCE electrode was studied by the current time method (it) with a time interval of 50s to test NO2 - The current concentration curve is shown in Figure 2. Figures 8 and 9 shown.

[0110] from Figure 8 It can be seen that each pulse response of the electrode system is very fast, NO2 - The oxidation current reaches a steady state within a few seconds. - With the addition of , the current increases significantly.

[0111] from Fig. 9 It can be seen that the response current is related to NO2 - The concentration ranges from 0.02 to 500 μM (0.001 to 23 mg·L -1 ) and 500-6000 μM (23-276 mg·L -1 ) range, the regression equations were Ip(μA)=1.5+0.3C(μM), Ip(μA)=122+0.03C(μM), and the correlation coefficients were 0.9985 and 0.9970, respectively. LOD was as low as 20 nM (0.001 mg·L -1 ), S / N=3, and the calculated sensitivity in the low concentration range is 4.23 μA μM -1 cm -2 .

[0112] Example 10

[0113] According to the steps of Example 1, 6 GCE electrodes were prepared to prepare Bi2Se3@MWNTs / GCE electrodes. The obtained 6 Bi2Se3@MWNTs / GCE electrodes were exposed to 1mM NO2 - Conduct current test and record the response current change within 6000s. The results are as follows: Figures 10-11 As shown. Fig.10 It can be seen that the 6 electrodes have a strong affinity for NO2 - The response currents of the samples were slightly different and had good reproducibility. Fig.11 It can be seen that the current drop within 6000s is almost negligible.

[0114] At the same time, the current response signal was measured after being placed at room temperature for 10 days, and the result was 90% of the initial value.

[0115] All of the above indicate that the Bi2Se3@MWNTs modified electrode has good stability, which is directly related to the strong connection between Bi2Se3 and MWNTs, which can reduce the aggregation and bundling of the composite material and greatly improve its stability and dispersibility.

[0116] Embodiment 11

[0117] Bi2Se3@MWNTs / GCE electrode was used to sample the interference substances, including NaNO3, KNO3, Na2CO3, NaCl, KCl, Na2SO4, CaCl2 and glucose, which are commonly found in water environments. The current time method was used to add 100 μM of different interference substances every 50 s until the concentration of 5 μM NO2 - The anti-interference detection study was carried out in PBS solution (pH=7). Fig.12 As shown. Fig.12 It can be seen that the detection of target molecules is almost unaffected by the above substances. This shows that the Bi2Se3@MWNTs modified electrode can still detect NO2 in the presence of high concentrations of interfering ions. - It has high sensitivity and selectivity.

[0118] Example 12

[0119] like Fig.13 As shown, the working electrode 1 is the Bi2Se3@MWNTs / GCE electrode prepared in the above embodiment, which includes a glassy carbon electrode, i.e., a GCE electrode 11, and a Bi2Se3@MWNTs composite material coated on the surface of the GCE electrode 11. The coated shape of the Bi2Se3@MWNTs composite material is circular, and preferably, the diameter of the coated diameter is 3 mm. Within the coating range, the coating amount of the Bi2Se3@MWNTs composite material on the GCE electrode 11 per square millimeter is 0.50-0.85 μg, preferably 0.71 μg.

[0120] The nitrite detection system includes an electrochemical workstation 4, a working electrode 1, a reference electrode 2, a counter electrode 3, and a test solution 6 contained in a test container 5, wherein one end of the working electrode 1, the reference electrode 2, and the counter electrode 3 are all connected to the electrochemical workstation, and the other ends of the working electrode, the reference electrode 2, and the counter electrode 3 are all immersed in the test solution 6. The electrochemical workstation 4 can also be connected to a computer 7 to display the signal generated by the electrochemical workstation 4 through the computer 7. The electrochemical workstation 4 in this embodiment adopts Chenhua CHI 660D (Shanghai), uses Ag / AgCl electrode as the reference electrode, and uses platinum wire as the counter electrode.

[0121] When the nitrite detection system of this embodiment is used to detect nitrite in a sample, the method is as follows:

[0122] The pH value of the sample containing nitrite is adjusted to 6.5-8, preferably 6.5-7.5, more preferably pH=7 using PBS buffer solution to obtain a test solution; a working electrode 1, a reference electrode 2 and a counter electrode 3 are inserted into the test solution so that the other ends of the working electrode 1, the reference electrode 2 and the counter electrode 3 are immersed in the test solution; the voltage of the electrochemical workstation is kept constant at 0.85V, and the current value is read after power is turned on; the nitrite content in the sample is obtained by converting the solution concentration value according to the above-mentioned current concentration curve.

Claims

1. An application of a Bi2Se3@MWNTs composite material in detecting nitrite, characterized in that: The following steps are involved: (1) Dispersing Bi2Se3 and MWNTs in a mass ratio of 0.5 to 1.5 in a dispersant and mixing them uniformly to obtain a Bi2Se3@MWNTs composite material, wherein the MWNTs are multi-walled carbon nanotubes, the dispersant includes at least one of DMF, water or tetrahydrofuran, and the concentration of the Bi2Se3@MWNTs composite material solution is 0.4 to 0.6 mg / mL; (2) Bi2Se3@MWNTs composite material solution was prepared at 0.55~0.85μg / mm 2 The coating amount is drop-coated on the surface of the pretreated glassy carbon electrode and dried to obtain a working electrode; (3) Adjust the pH value of the sample solution containing nitrite to 6.5-8.0 to obtain a test solution; insert a working electrode, a reference electrode, and a counter electrode into the test solution so that the other ends of the working electrode, the reference electrode, and the counter electrode are immersed in the test solution; maintain a constant voltage and read the current value; convert it into a solution concentration value based on the current concentration curve.

Citation Information

Patent Citations

  • And working electrode and nitrite detection system

    CN212622375U